INITIATION-RESPONSE-EVALUATION (IRE) TECHNIQUE COLLABORATED WITH PANEL DISCUSSION ACTIVITY IN TEACHING SPEAKING SKILL - Joni, Dewa Ayu Ari Wiryadi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2019)
This study was conducted to present the improvement of the students after the researcher applied IRE collaborated with panel discussion technique in the teaching-learning processes to stimulate the students to speak English actively. The subject of this study was the IV B students of ELSP FTTE Unmas Denpasar in academic year 2016/2017. The subject under study was 29 students. They could improve their speaking skill such as grammar, fluency, pronunciation and comprehension achievement after learning through IRE collaborated with panel discussion technique. The present classroom action study was conducted based on the result of pre-test which was65.17, which showed the students’ speaking skill was low. To improve their speaking, the researcher conducted a classroom action research which was conducted in two cycles which in each cycle was consisted of two sessions. There were some research instruments used by the researcher to collect the data, namely: tests, questionnaires and observational sheet. The result of the data analysis of the reflection scores in cycle I, cycle II and cycle III showed the increasing mean figure of 71.9, 75.83 and 81.72. There was a significant increase between the mean figure of cycle I, cycle II and cycle III. These findings showed that IRE technique collaborated with panel discussion activity could improve the students’ speaking skill. The result of the analysis of the questionnaire score showed the comparative percentage figures of 67.76%, 29.52%, 2.72%, 0% and 0% for the total responses of questionnaire items options strongly agree, agree, neutral, disagree and strongly disagree respectively. It showed that the subjects’ responses toward the technique were positive. This study provided empirical evidences on teaching English speaking skill toward adult learners using IRE technique collaborated with panel discussion activity.